Catches of male olive moths, Prays oleae, in pheromone traps in relation to numbers of eggs and larvae found in olive fruits, in Crete - Polyrakis, Ι. (ENTOMOLOGIA HELLENICA, 1983)
In two groves of the Chania area, male olive moths, Prays oleae (Bernard) (Lepidoptera: Hyponomeutidae), caught in pheromone traps and eggs and young larvae in young fruits were counted weekly or daily in May, June and July. At Mournies, the first rise in the curve of male captures was observed during the last week of May with a maximum on the 18th in 1980 and on the 10th of June in 1981, and the last captures at the end of June-beginning of July. At Chrysopigi, the maximum of captures in 1981 was on the 5th of June. In all instances the time of maximal moth captures coincided with peaks in oviposition activity, followed after an interval of two weeks by peaks in the number of young larvae found in the fruits.